A severe complication of pulmonary vein angiography. Issue 6 (June 1979) - Alpert, B S; Culham, J A
Abstract : A pulmonary vein angiogram was performed using a pressure injection with the tip of an end and side hole catheter in a near-wedge position; extravasation of contrast material into a bronchus occurred, causing severe bronchoconstriction. It may be possible to avoid this complication by the use of an end hole balloon catheter in the wedge position, slow flow rates of contrast material, and low pressure injections.